2012
DOI: 10.1136/bmjqs-2011-000299
|View full text |Cite
|
Sign up to set email alerts
|

Identifying, understanding and overcoming barriers to medication error reporting in hospitals: a focus group study

Abstract: Study results may lead to a better understanding of the barriers to medication error reporting, why these barriers exist and what can be done to successfully overcome them. These results could be used by hospitals to encourage reporting of medication errors and ultimately make organisational changes leading to a reduction in the incidence of medication errors and an improvement in patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
165
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(199 citation statements)
references
References 40 publications
16
165
5
Order By: Relevance
“…physicians, pharmacists and nurses) and in-depth interviews. 'Major changes of this study to improve the process and improve medication error reporting are not going to occur overnight but will require much deliberation, dedication and resource allocation', (Hartnell, 2012). The study suggests that the small number of positive facilitators suggested by these study participants indicate that 'some fairly simple changes could make a positive difference in medication error reporting at these organizations and others facing similar challenges', (ibid).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…physicians, pharmacists and nurses) and in-depth interviews. 'Major changes of this study to improve the process and improve medication error reporting are not going to occur overnight but will require much deliberation, dedication and resource allocation', (Hartnell, 2012). The study suggests that the small number of positive facilitators suggested by these study participants indicate that 'some fairly simple changes could make a positive difference in medication error reporting at these organizations and others facing similar challenges', (ibid).…”
Section: Introductionmentioning
confidence: 99%
“…Also, we need to specify the possible strategies that could improve and encourage nurses and physicians to report medical errors. Needless to say that 'limited information is available on why these barriers still exist or about methods to overcome these barriers successfully', (Hartnell, 2012). Hartnell continues that 'such information must be obtained before the improvements of patient safety can be realized through lessons learned from the reporting of medication errors', (ibid).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nurses are the healthcare professionals who most frequently report errors, many continue to harbor fears about reporting them (Bayazidi, Zraezadeh, Zamanzadeh, & Parvan, 2012;Cook, Hoas, Guttmannova, & Joyner, 2004;Espin, Lingard, Baker, & Regehr, 2006;Hartnell MacKinnon, Sketris, & Fleming, 2012;Osmon et al, 2004;Rowin et al, 2008;Prang & Jelsness-Jorgensen, 2014;Uribe, Schweikhart, Pathak, Dow, & Marsh, 2002). In many institutions, the workplace culture regarding error reporting remains one of blame, and nurses are often concerned about personal repercussions associated with reporting errors (Blair, Kable, Courtney-Pratt, & Doran,2015;Castel, Ginsburg, Zaheer, & Tamin, 2015;Cook et al, 2004;Espin et al, 2006;Jeffe et al, 2004;Stratton, Blegen, Pepper, & Vaughn, 2004;Taylor et al, 2004;Uribe et al, 2002).…”
mentioning
confidence: 99%
“…However we acknowledge that the issue of the frequency of medical errors in the critical care setting is controversially discussed in medical literature [30,31] and our findings might also be influenced by other factors such as underreporting as a consequence of fear of punitive measures [32,33]. In our study, most administration errors occurred on the wards, where work under time pressure due to shortage of personnel and heavy workload are recognized risk factors [34].…”
Section: /22mentioning
confidence: 69%